Evaluation of biofilm formation and corrosion behaviour of SAE 1010 carbon steel in SRB cultures by microscopic techniques and electrochemical impedance spectroscopy - Viera, Marisa (2017)
Biofilms cause various problems such as medical infections, fouling of water cooling system, product contamination, and microbiologically influenced corrosion (MIC). MIC accounts for as much as 20% of all forms of corrosion, amounting to billions of dollars in losses each year. Among bacteria related to MIC, sulfate reducing bacteria (SRB) are most often blamed. The ubiquity of these bacteria leads to a variety of impressive industrial, economic and ecological effects because of their proneness to generate large quantities of H2S. SRB are the main reason to cause the MIC by accelerating corrosion rate, inducing stress corrosion and pitting corrosion. The aim of this study was to evaluate the corrosion associated with the formation of SRB biofilms on carbon steel surfaces.